2000
DOI: 10.1638/1042-7260(2000)031[0303:mamawa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Associated With a New Mycoplasma Species From Captive American Alligators (Alligator Mississippiensis)

Abstract: Nine of 74 American alligators (Alligator mississippiensis) from a captive Florida herd of 3-4-m-long, 200-350-kg, adult males greater than 30 yr of age died within a 10-day period during 1995. Nonspecific clinical signs included anorexia, lethargy, muscle weakness, paraparesis, bilateral white ocular discharge, and various degrees of periocular, facial, cervical, and limb edema. Pneumonia, pericarditis, and arthritis were found on postmortem evaluation of the spontaneously dead and euthanatized alligators. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Mycoplasmal infection usually presents as a chronic, clinically silent disease with high morbidity but low mortality [2, 4-7, 9, 22-26]. In contrast, during the initial 1995 epizootic of captive American alligators, mortality was rapid with >80% of the population dying within a 6-month period [29]. Moreover, histological examinations confirmed that there was multisystem involvement with pneumonia, endocarditis, arthritis, and myocarditis [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mycoplasmal infection usually presents as a chronic, clinically silent disease with high morbidity but low mortality [2, 4-7, 9, 22-26]. In contrast, during the initial 1995 epizootic of captive American alligators, mortality was rapid with >80% of the population dying within a 6-month period [29]. Moreover, histological examinations confirmed that there was multisystem involvement with pneumonia, endocarditis, arthritis, and myocarditis [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the natural host, the American alligator, we initially used the IT route of infection because that was the original route used in early infection studies [27,29,41]. We also used the results from these studies to inform our choice of infectious doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rainbow trouts can become anorectic under stressful conditions [ 27 ]. Even crocodiles develop anorexia and lethargy during infection [ 28 ], which demonstrates the uniformity of the response. In sum, the immune, endocrine, and nervous systems have evolved over hundreds of millions of years, and to understand diseases in humans, including CIDs, the long evolutionary history of these supersystems has to be taken into account.…”
Section: Evolution Of the Supersystems And Their Interactionsmentioning
confidence: 99%